Decentralization and implementation of climate change policy in Uganda - Esbern Friis-Hansen; Bernard Bashaasha; Charles Aben (Danish Institute for International Studies (DIIS), 2013)
This working paper is the first of two working papers that presentings findings from the Climate Change and Rural Institutions (CCRI) research program on how meso-level institutions in Uganda are responding to climate change and extreme climate events. This working paper analyses national policies that to support climate change mitigation and adaptation and their implementation modalities. The second working paper focuses on the meso-level institutional dynamics of how climate change action inside within as well as outside the framework of climate change policies. For more information about CCRI, see http://subweb.diis.dk/sw113176.asp The CCRI research program undertakes empirical fieldwork in Soroti, Amuria and Katakwi districts located in of Teso region, Eeastern Uganda. The research examines how extreme climate events such as the 2007 floods and subsequent severe floods and droughts , as well as the gradual change in weather patterns, are affecting meso-level institutions.
Keywords: 300